THE INTEGRATION OF RELIGION AND CULTURE IN THE PREPARATION OF A KING WITHIN BABAD NGAYOGYAKARTA HB IV-V (SB 169) - Arsanti Wulandari (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
Cross-cultural interactions are commonplace. The fact that Javanese people are very multicultural is one of the perfect examples. The text of Babad Ngayogyakarta Hamengkubuwana IV-V records this phenomenon. The text, a copy written in 1881CE (during HB VII period), is indeed an important cultural document. Bbd.Ngy.HB IV-V contains an account of the coronation of HB IV and stories how he and his successor (HB V) governed the kingdom. A close reading of this text gives an overview of how Javanese culture coexists in harmony with Islam. Islam is seen not only as a religion but also an identity that exists within the kings. However, Javanese culture is also irrevocable for Javanese leaders. The text said that the king (when he was still a teenager) must read the Qur'an everyday. This is referred to in the text with the word ngarbi that is interpreted as Arabic and refers to an Arabic letter (referring to the Qur'an). The king not only had to study the religion but also to read Javanese literary books, namely Babad Mentawis, Serat Rama, and Astabrata, all of which provide wisdoms by giving examples of archetypal behaviors and teachings for a king. Habituation with two these pillars side by side, religion and cultural traditions, in preparing the king shows the importance of character. Religion is a pillar that must be strong within a leader’s character, but he must not abandon the local culture of high value. The combination of the two pillars becomes the ideal character of a Javanese leader.